State of dietetics practice in Ghana - Aryeetey, R.N.; Boateng, L.; Sackey, D. (Ghana medical journal, 2014)
OBJECTIVE: Prevalence of obesity and related diseases has increased in Ghana. Dietitians have essential skills to prevent and manage dietary diseases. However, little is known about dietetic practice in Ghana. This paper describes the history and current state of dietetics practice in Ghana.METHODS: A questionnaire was administered to 13 dietitians and six dietetic interns in February 2012. The questionnaire collected data on perceptions about dietetics practice, career progression, and challenges in dietetics practice in Ghana. Key informant interviews (KII) on history of dietetics in Ghana were also held with four retired dietitians, and two dietetics educators. Additional KII were conducted with the Chief dietitian, two officers of the Ghana Dietetic Association, and three other dietitians. Most KII were conducted face-to-face but a few were only possible via telephone. Some of the KII were audio-recorded, in addition to handwritten notes. Following transcription of audiorecorded interviews, all data were subjected to content analysis.RESULTS: Dietetic practice in Ghana has evolved from low-skilled cadre (catering officers) offering hospital-based meal services to the current era of available trained dietitians providing diet therapy in diverse settings. However, 80% of the 35 dietitians identified are working in Accra. In three regions of Ghana, there are no dietitians. There remain limited opportunities for continuous learning and professional career advancement. Additionally, there are many unqualified dietitians in practice.CONCLUSION: A huge unmet need for dietitians exists in all regions of Ghana, except Greater Accra. Bridging this gap is essential to increase access to dietetic care throughout Ghana.
Keywords: dietetics; Ghana; history; professional practice; situational analysis